Multiparametric risk predictions for morbidity and mortality in patients with pulmonary arterial hypertension: insights from a nation-wide registry - Basarici, I; Kaymaz, C.; Akbulut, M.; Yildirimturk, O.; Asker, M.; Yaylali, T.; Tokgozoglu, L. (Oxford Univ Press, 2024)
[Abstract Not Available]
European-Society-of-Cardiology Congress (ESC) -- AUG 30-SEP 02, 2024 -- London, ENGLAND